Effect of Skirt on the Bearing Capacity of Circular Footing on Sand - Satria, Isvan Fajar; , Anto Budi Listyawan, S.T., M.Sc; , Ir. Renaningsih, M.T (2016)
Bearing capacity is the most important factor in designing the foundation. It is necessary to find an effort to improve the bearing capacity. Skirts that are attached on the bellow of footing can be used as an alternative of it. They are used to improve the bearing capacity of shallow footing on sand soil. This study is performing twelve laboratory experiments on steel circular footing with different diameters and different skirt length, on the sand soil by keeping the same formation of water content and compaction method. From the accomplished laboratory tests, it was found that skirts are very effective to improve the ultimate bearing capacity, as they increase the length, the ultimate bearing capacity increases up to 4.70 times for the current study condition. Skirts also reduce the settlement. The settlement generally decreases, when it is observed on the same value of load, 2.00 kN. Skirted circular footing with the longest skirt has the best condition of settlement.